IMPLEMENTATION OF ONLINE PRACTICUM AT BIOLOGY EDUCATION STUDY PROGRAM, UNIVERSITAS AHMAD DAHLAN - Nani Aprilia; Hani Irawati (Universitas Negeri Padang, 2022)
COVID-19 pandemic has changed the order of people's lives, and is a factor that has a major influence on learning, one of which is biology practicum at the university level. This study aims to evaluate the online biology practicum in the Biology Education Study Program, Universitas Ahmad Dahlan. This study uses a stake evaluation model. Determination of sample using the Slovin method and obtained 132 students. Collecting data by observation and questionnaires. Descriptive quantitative data analysis. Based on the findings, it is known that in the aspects of preparation and planning; preparation of practicum plan sheets, practicum rules, and practicum implementation instructions; categorized as very good. In the aspect of implementation, it is categorized as good, and learning outcomes are categorized as good.